2019
DOI: 10.1080/20961790.2019.1630944
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem imaging as a complementary tool for the investigation of cardiac death

Abstract: In the past 2 decades, modern radiological methods, such as multiple detector computed tomography (MDCT), MDCT-angiography, and cardiac magnetic resonance imaging (MRI) were introduced into postmortem practice for investigation of sudden death (SD), including cases of sudden cardiac death (SCD). In forensic cases, the underlying cause of SD is most frequently cardiovascular with coronary atherosclerotic disease as the leading cause. There are many controversies about the role of postmortem imaging in establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Moreover, by means of a radiological investigation, different heart abnormalities can be highlighted [ 126 ]. As recently reported, modern radiological methods, such as multiple detector computed tomography (MDCT), MDCT-angiography, and cardiac MRI have been introduced into post-mortem practice for the investigation of SD, including cases of SCD [ 127 ]. A recent retrospective study studied the role of forensic post-mortem CT in order to define the cause of death, especially in cases of acute heart insufficiency or respiratory failure [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by means of a radiological investigation, different heart abnormalities can be highlighted [ 126 ]. As recently reported, modern radiological methods, such as multiple detector computed tomography (MDCT), MDCT-angiography, and cardiac MRI have been introduced into post-mortem practice for the investigation of SD, including cases of SCD [ 127 ]. A recent retrospective study studied the role of forensic post-mortem CT in order to define the cause of death, especially in cases of acute heart insufficiency or respiratory failure [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…PMCT allows the visualization and quantification of coronary calcifications before the autopsy. There are many controversies about how to interpret coronary calcifications on PMCT and how to interpret their presence for cases of sudden death [3,[15][16][17]. Some recent postmortem studies demonstrated that Agatston scoring zero or low cannot rule out the presence of extensive stenosis [16] and that CACS can neither confirm nor exclude death due to ACAD [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gas leads to a complete loss of signal in MR. Gases formed by autolysis can significantly interfere with imaging. On the other hand, the detection of myocardial infarction is as good in postmortem MRI as in living patients [7]. MRI is currently the method of choice for postmortem imaging of neonates and paediatric cadavers [3].…”
Section: Review Of the Literaturementioning
confidence: 99%